2019
DOI: 10.1186/s12889-019-7263-6
|View full text |Cite
|
Sign up to set email alerts
|

1-year follow-up of the mental health and stress factors in asylum-seeking children and adolescents resettled in Germany

Abstract: Background Asylum-seeking children and adolescents (ASCs) who have resettled in Western countries show elevated rates of psychological distress, including Posttraumatic Stress Symptoms (PTSS), depression, and anxiety. Most longitudinal data suggest a relatively stable course of symptoms during the first years in exile. However, no longitudinal examination of the mental health of ASCs, who resettled in Europe in the wake of the 2015–17 European migrant crisis, has been conducted so far. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 39 publications
7
43
1
4
Order By: Relevance
“…These ndings are in line with several studies from other European countries reporting high PTSS rates from 20% [5] to 76% [6]. On average, symptoms tend to be stable over time [7] even though another recent study by Müller et al [8] indicated a signi cant reduction in PTSS severity after 12 months. However, the rates for clinically relevant PTSS (38%) were still high.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…These ndings are in line with several studies from other European countries reporting high PTSS rates from 20% [5] to 76% [6]. On average, symptoms tend to be stable over time [7] even though another recent study by Müller et al [8] indicated a signi cant reduction in PTSS severity after 12 months. However, the rates for clinically relevant PTSS (38%) were still high.…”
Section: Introductionsupporting
confidence: 89%
“…However, participants can directly bene t from successful treatment and long-term symptom reduction can be achieved. Even for the control group who will not receive the stepped-care, we do not expect any harm: in two previous studies [2,8] we assessed young refugees' mental health without providing further interventions. No serious or adverse events were reported during the two studies.…”
Section: Ethical Considerations Monitoring and Safetymentioning
confidence: 89%
“…The epidemiological data on mental health are scarce as state fragility also impacts health surveillance efforts. However, research on asylum-seeking youth from Afghanistan, Syria, Eritrea and Iraq found persistently high prevalence of emotional and behavioural problems ( Bronstein et al, 2013 ) posttraumatic stress symptoms ( Müller et al, 2019 ) and hair cortisol concentrations ( Sierau et al, 2019 ) after resettlement in Europe. A study of Kosovar Albanians shortly after the 1998-99 Kosovo war found that 17% of youth and adults over age 15 suffered from posttraumatic stress disorder ( Lopes Cardozo et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, participants can directly benefit from successful treatment and long-term symptom reduction can be achieved. Even for the control group who will not receive the stepped-care, we do not expect any harm: in two previous studies [ 2 , 8 ], we assessed young refugees’ mental health without providing further interventions. No serious or adverse events were reported during the two studies.…”
Section: Methodsmentioning
confidence: 99%
“…These findings are in line with several studies from other European countries reporting high PTSS rates from 20% [ 5 ] to 76% [ 6 ]. On average, symptoms tend to be stable over time [ 7 ] even though another recent study by Müller et al [ 8 ] indicated a significant reduction in PTSS severity after 12 months. However, the rates for clinically relevant PTSS (38%) were still high.…”
Section: Introductionmentioning
confidence: 99%